Stabilization of enzymes in micro-emulsions for ultrasound processes - Martins, Madalena A. (2015)
Oil-in-water proteinaceous micro-emulsions are described as novel methodology for the stabilization of enzymes. Proteins are tightly packed at the oil-water interface of micro-emulsions and it was found that micro-emulsions of laccases enzymes have enhanced stability under high temperatures and ultrasound fields (see graphical abstract scheme and data). This stabilization technique seems to be a promising methodology to apply on other enzyme-based processes where the operational conditions required high levels of mass transport.